Therapeutic drug monitoring of immunosuppressant drugs in Marmara University Hospital - AKICI, AHMET; KARAALP, ATİLA; ONAT, FİLİZ; YANANLI, HASAN RACİ (LIPPINCOTT WILLIAMS & WILKINS, 2004)
Immunosuppressive therapy is the most crucial treatment of organ-transplanted patients. Both cyclosporin and tacrolimus have become a part of the standard immunosuppressive therapy for prevention of rejection. However, lower levels of these drugs are associated with insufficient therapy and eventually result in rejection of the organ, and, on the contrary, higher levels are associated with toxicity to certain organs such as liver and kidneys. Therefore, the levels of these drugs in body fluids should be monitored for the prevention of unwanted situations. In this retrospective study, the authors evaluated the 18-month profile of blood drug concentrations of cyclosporin and tacrolimus in patients admitted to the TDM Unit of the Marmara University Hospital (Istanbul, Turkey) between June 2000 and November 2001. A total of 578 blood samples (347 cyclosporin and 231 tacrolimus) from 134 patients (88 for cyclosporin, 46 for tacrolimus) were evaluated in this period. The therapeutic trough ranges were accepted as 100-350 ng/mL for cyclosporin and 5 20 ng/mL for tacrolimus, and levels below or above the identified levels were accepted to be subtherapeutic or toxic. Most of the results were found within the range of therapeutic levels (67.48% for cyclosporin and 82.71% for tacrolimus). Subtherapeutic levels were found in 19.92% of all cyclosporin and 10.53% of all tacrolimus assays, whereas toxic levels were seen in 12.60% and 6.77% of cyclosporin and tacrolimus results, respectively. In conclusion, this study gives information about the TDM practice in institutional clinical laboratory and also indicates the importance of critical information such as sampling time for individual decision making in dosage regiment.
Keywords: cyclosporin; immunosuppressant; tacrolimus; therapeutic drug monitoring; CYCLOSPORINE; PHARMACOKINETICS; TRANSPLANTATION; RECIPIENTS; 2-HOUR; TROUGH